Pengaruh Pendidikan, Pelatihan, Dan Pengalaman Kerja Terhadap Prestasi Kerja Karyawan Pada PT. Sami Surya Perkasa Sukoharjo - Mardiyanti, Yuli; Nur Achmad, S.E., M.Si. (2017)
The research objective was to determine the influence of education, training and work experience to employee performance of PT. Sami Surya Perkasa Sukoharjo by partial and also simultaneous. This research was using primer data type what was obtained by propagating the questioner to respondents becoming research sample. The population in this research of entire employees of PT. Sami Surya Perkasa Sukoharjo with sample counted 50 peoples by using saturated purposive sampling. The data analyse technique was using the multipplied linear regression analysis. Pursuant to result of calculation SPSS 20.00 from t test obtained a education variable has a significant equal to 0,002 < 0,05 so H0 refused and H1 accepted, training variable has a significant equal to 0,000 < 0,05 so H0 refused and H2 accepted and work experience variable has a significant equal to 0,000 < 0,05 so H0 refused and H3 accepted. Result of F test o btained probability significant equal to 0,000 < 0,05 so H0 refused and H4 accepted, so that this research was education, training and work experience variable having an effect on positive and significant to employees performance. Determination coefficient (R 2 ) obtained result equal to 0,466 meaning that education, training and work experience could be explain to variation of change employees performance equal to 46,6%, explainable the rest other variable was which do not there were in research model.